Avaliação de competência clínica de médicos residentes de Urologia na realização de exame urodinâmico - Honji, Valter Yasushi (2014)
Clinical skills assessment is an essential step in the medicine students´ graduation and must be done by the teacher through direct performance observation in a real situation. The usage of Mini-Cex is an additional formative and summative evaluation option that assesses pre or post graduates students´ medical expertise. Objectives: Evaluate clinical residents competence on performing urodynamic exames; quantify performance development after feedback attainment, quantify technical improvement quality of urodynamic examination by the resident doctor ; quantify the time spent in applying the Mini-Cex by the observer; detect and quantify medical disabilities during urodynamic examination, evaluate the reliability and internal consistency of the Mini exercise Clinical Evaluative ( Mini-Cex ) for the urodynamic examination. Methods: A quantitative and qualitative study conducted with graduated students in urology during the performance of urodynamic examination, through the Mini-Cex instrument application, which is based on a Likert Scale of 9 categories, which grades 1 to 3 refer to unsatisfactory performance ; 4 to 6 to satisfactory performance and 7 to 9 the exemplary performance . This instrument allowed residents' performance assessment in achieving the urodynamic examination by the researcher on the following questions: on interviewing, physical examination, clinical reasoning skills, humanistic and professional qualities, orientation, organization/efficiency and overall, clinical competence. At the end of the consultancy the researcher conducted a feedback to each student pointing their failures and successes in achieving the urodynamic testing, setting up formative assessment. Results: The findings recommend the usage of the Mini-Cex in performing urodynamic studies (Cronbach's alpha between 0.8 and 0.9) and performing feedback advantages on development of residents´ learning